BRANDING: MENINGKATKAN BRAND AWARENESS WISATA PANTAI LON MALANG SOKOBANAH KABUPATEN SAMPANG - Fazlurrahman Adenan Ramdani Saleh; Aileena Solicitor Costa Rica El Chidtian; Aphief Tri Artanto (JURNAL IMAJINASI, 2022)
Beach tourism is very popular with many local and foreign tourists. The beach is a prima donna for foreign tourists who come to visit the State of Indonesia, the beach can also be a tool to develop the potential and economy of the community around the coast. The main factor supporting the development of potential and the economy is marked by the number of tourists who come to visit. In designing a brand on Lon Malang beach tourism, Sokobanah which is informative and creative in the form of Brand Awareness of Lon Malang Beach Tourism. Brand awareness itself aims to provide creative and informative information, and can indirectly improve a good image for Sampang Regency. This design uses a qualitative method with 2 stages, namely in-depth interviews and field observations. The approach taken using these 2 stages can produce a design concept with the keyword "Unforgettable Vacation" as a means to see the beauty of the sun, a stretch of clean and beautiful white sand. This brand awareness is designed as a communication medium to develop Lon Malang Sokobanah Beach Tourism to be better known by the wider community, not only tourists on the island of Madura, of course it can reach tourists outside the island and abroad.